Higher Compared to Lower Protein Show Favourable Effects on Weight Loss and Fat Mass – A Systematic Review and Meta-Analysis. (7th June 2021) - Vogtschmidt, Yakima; Raben, Anne; Faber, Ilona; de Wilde, Claudia; Lovegrove, Julie; Givens, D Ian; Pfeiffer, Andreas; Soedamah-Muthu, Sabita
Abstract: Objectives: Our objective was to conduct a systematic review and meta-analysis of the effects of higher versus lower dietary protein consumption on obesity and diabetes related measures in adults, using the most up-to-date evidence from randomised controlled trials (RCTs). Methods: A systematic search with predefined keywords was conducted in PubMed, Scopus, and Web of Science up to January 2020 and subsequently updated in November 2020. Adult populations (age range: 23 to 68 years; mean body mass index (BMI): 33 ± 3.3 kg/m 2 ) were included and the percentage of men/women was 35%/65%. Data were independently extracted with the use of standard forms in "Covidence" and with double data-entry checks. Random effects meta-analyses were conducted to pool the standardised mean differences (SMD) and 95% confidence intervals (CI). The main study outcomes were weight loss, fat mass, BMI, waist circumference, fasting glucose, fasting insulin and glycated haemoglobin (HbA1c ). Results: Fifty-seven articles reporting on 54 trials were included, with 2185 and 2159 participants in the higher protein (HP) and lower protein (LP) groups, respectively. The mean daily energy intakes were 1764 ± 455 kcal in the HP group and 1768 ± 462 kcal in the LP group. The percentage of protein, carbohydrate, and total fat of the total daily energy intake (E%) were 28%, 41% and 30% in the HP group and 18%, 54% and 28% in the LP group. Significant effects of the HP compared to LP diets were found for weight loss (pooled SMD −0.13, 95% CI: −0.23, −0.04) and fat mass (pooled SMD −0.14, 95% CI: −0.25, −0.04), with small to moderate heterogeneity. This is equivalent to a greater weight loss of 0.67 kg (95% CI: −1.14, −0.19) and a greater reduction in fat mass of 0.57 kg (95% CI: −0.95, −0.19) after the HP compared to LP diets. No significant differences were found for the other study outcomes. Conclusions: This meta-analysis of 54 trials showed that higher (28 E%) compared to lower protein diets (18 E%) had small but favourable effects on weight loss and fat mass, which are relevant indicators for the development of obesity and its complications. Funding Sources: None.